Pengaruh Gaya Mengajar Komando Terhadap Hasil Belajar Tolak Peluru Gaya Menyamping Pada Siswa SMA - Edita A.M. Pinangkaan (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to examine the application of the commando teaching style on the learning outcomes of sideways style sweating at the high school students of State I Kawangkoaan. The method used in this research is the experimental method. The sample used was the students of the State High School I Kawangkoaan, totaling 20 samples, which were divided into two groups, namely the experimental group with a command teaching style totaling 10 samples and the control group receiving no treatment totaling 10 samples. The instrument used in this study was a "sideways test of shot put style". The data collection technique in this study was to conduct a preliminary test and a final test of the sideways force decay for both groups. From the calculation of the research hypothesis testing, it is obtained that tcount is 3.13. Based on the t distribution table at 0.05 with degrees of freedom n1 + n2-2 = 10 +10-2 = 18, it is obtained ttable worth 2.101. So tcount is smaller than ttable, namely tcount = 3.13 > ttable = 2.101. Based on the test criteria, if tcount is greater than ttable (tcount > ttable) then reject Ho and accept HA. Thus the conclusion of the test is that the average increase in side-by-side shot put learning outcomes in the experimental group taught with the commando style of teaching is better than the average increase in side-by-side shot put by the control group, meaning that there is a difference between the two groups. Thus, it can be concluded that the commando teaching style have an effect on increasing the sideways style of shot put in high school students I Kawangkoan State.